Pengaruh Faktor Demografi terhadap Literasi Keuangan - Raja Ria Yusnita; Muhammad Abdi (COSTING : Journal of Economic, Business and Accounting, 2018)
Financial knowledge is one of the important aspects in life today. This study aims to determine the level of financial literacy in motorbike workshop SMEs in Kec.Siak Hulu Kab. Kampar and analyze whether demographic factors consisting of education level, income level, duration of business and age affect the level of financial literacy among workshop entrepreneurs. The number of samples in this study are 50 workshop entrepreneurs with the research method used is the survey method by obtaining data through questionnaires. While the analysis used in this test is binary logistic regression analysis. The results showed that the level of financial literacy for business people was in the low category with a percentage of 48%. The variables that influence the level of financial literacy are income level variables and besides these variables which consist of education level, duration of business and age does not affect the level of financial literacy for business actors. keywords: Financial Literacy, Education Level, Income Level, Duration, Age